IMAGE – Task 4.5 Tracer Test at Krafla High Temperature Geothermal Field June 21st – August 17th 2016 - Gadalia, Alain; Hersir, Gylfi Páll; Óskarsson, Finnbogi (Zenodo, 2016)
A reservoir tracer test was conducted in Krafla in summer 2016 as a part of the IMAGE project.Three liquid-phase tracers were injected into well K-39; two naphthalene sulfonate molecules (2,6-NDS and 2,7-NDS) and potassium iodide (KI). The tracers were only observed in one out of fivemonitoring wells; well K-19. The first tracer breakthrough was observed within 3 days of injectionand peak recovery at about 15 days afterinjection. A comparison of the recovery curves of the conservative KI and the less thermally stable NDSmolecules reveals no evidence of thermal degradation of the latter.Calculation of the apparent linear velocities gives values of the same order as for the 2013-2015Krafla tracer test. FP7